Quantum Goos-Hänchen switch in graphene junctions - Z B Zhang; Rui Wang; Baigeng Wang; D Y Xing (New Journal of Physics, 2023)
Goos-Hänchen (GH) shift, an interference phenomenon describing the lateral shift of the reflected beam along the interface during total internal reflection, has attracted great interests in the field of quantum transport in two-dimensional materials. In particular, the GH effect generates a novel pseudospin-dependent scattering effect in graphene, which in turn results in an $8e^{2}/h$ conductance step in the bipolar junctions. Here, we reveal that a barrier region with effective barrier strength χ can greatly enrich the GH effect in graphene junctions. In contrast to the conventional case where the negative shift is allowed only in the p - n junction, the thin barrier enables both negative and positive spatial shifts in p I n and n I n junctions, where I represents the barrier region. More interestingly, the lowest channel degeneracy can be efficiently varied by tuning χ in both the symmetric p I n I p and the asymmetric pn I p junctions, leading to a highly controllable switch that switches the conductance between $8e^{2}/h$ and $4e^{2}/h$ . These results advance the knowledge of GH effects in electronic materials and suggest experimental avenues for its observation and manipulation.